S. M. AMADAE, Prisoners of Reason: Game Theory and Neoliberal Political Economy; HUNTR HEYCK, Age of System: Understanding the Development of Modern Social Science; EGLĖ RINDZEVIČIŪTĖ, The Power of Systems: How Policy Sciences Opened Up the Cold War World: New York 2016, Cambridge University Press, 334 s.; Baltimore 2015, John Hopkins University Press, 258 s.; Ithaca – London 2016, Cornell University Press, 292 s. - Sommer, Vítězslav (Dějiny – teorie – kritika, 2019)
Review.